Spacecraft Trajectory Design Regarding Van Allen Belts by Honey Bee Optimisation Algorithm - Iman Shafieenejad (فصلنامه علوم و فناوری فضایی)
This research aims to optimize the trajectory of a low-thrust spacecraft carrying biological cargo. The objective is to minimize the radiation exposure from the Van Allen belts, the optimal criterion for the control problem concerning orbital transfers from low orbits to high orbits. Since the minimum radiation stress criterion introduced in this article is unconventional, solving this optimal control problem is complex, necessitating using the honey bee optimization algorithm.The trajectory optimization in this study involves rewriting the motion equations based on the control variables and solving these newly defined equations using the honey bee optimization method. The primary advantage of this approach is its integration of optimal control theory with population-based optimization methods, employing a global approach. In the novel method presented, the optimal control problem is simplified by redefining the differential equation system, and the results demonstrate both accuracy and ease of solution.Based on the results obtained from the comparison between the optimal criterion of minimum time and minimum radiation stresses presented in this article, the minimum radiation stress criterion causes an increase of 8.89% in transfer time. However, this criterion significantly reduces exposure to magnetic radiation, which is crucial in the transfer to high orbits.